INDONESIA'S POLICY REGARDING TO COMBAT WITH IUU FISHING THROUGH JOKO WIDODO'S GOVERNMENT SINKING SHIPS POLICY (2014-2019) - Elvina Mesha Nurul Dewi; Dairatul Maarif (Sriwijaya Journal of International Relations, 2022)
This study aims to describe Indonesia's policies in maritime security related to IUU fishing through the sinking ships policy during the 2014-2019 period of Joko Widodo's administration. The research method used is descriptive qualitative research. In this study, the author uses the theory of foreign policy, the concept of maritime security, and the concept of IUU Fishing to conduct the analysis in this study. The results of this study are the reason why the government's used to issue this policy based on efforts to realizing Joko Widodo's vision to make Indonesia a global maritime fulcrum, in addition to the existence of a national law that regulates the implementation of the sinking ships policy, with the results of research that the implementation of the foreign sinking ships policy was considered quite effective in reducing the number of illegal fishing in Indonesia. See the number of sunken boats has decreased in certain years, and the fisherman's exchange rate during 2015-2019 has increased every year, the average income of fishermen has increased each year during 2015-2019.